ANALYSIS OF EDUCATIONAL CHALLENGES FACED BY UNIVERSITIES DURING COVID 19: A CASE STUDY OF SOUTHERN PUNJAB UNIVERSITIES - Hashmi, Dr Arshad Hussain; Nadeem, Dr. Muhammad Asif; Ms. Zaib Un Nisa; Dr Farzana Rashid (Journal of Arts & Social Sciences, 2022)
COVID 19 devastation affected humanity socially and economically whose impacts would remain for many decades. One sector of human life which was affected badly has been education sector. The students of educational institutions suffered a lot all around the globe. The present descriptive research analyzed those effects and suggested solutions to cope with the aftereffects being produced. Major objective of this research was to identify the educational issues acclaimed due to pandemic in the higher educational institutes and to analyze the current situation prevailing in the higher educational institutes due to COVID 19. The researchers recommended the solutions to come out of this situation by using mix method of research and took the stakeholders higher education teachers and taught on board for their contribution into research. A semi structured survey, interview and observation check list was taken as a tool for collecting data from the population. Multistage sampling technique was used to collect data from the samples. Randomization and convenient sampling technique was used to collect data from the graduates and teachers who underwent the pandemic teaching and learning process in Pakistani Universities. Overall 400 students and 20 teachers took part in the process of research. The results and findings attained from these participants showed that COVID disturbed their teaching and learning activity a lot and they faced immense problems during two years. It was found that this irreparable loss seemed to prevail in their future and it needed to be compensated through make up classes or refresher courses in their perspective fields.